2011
DOI: 10.1007/s10549-011-1457-7
|View full text |Cite
|
Sign up to set email alerts
|

bc-GenExMiner: an easy-to-use online platform for gene prognostic analyses in breast cancer

Abstract: Gene prognostic meta-analyses should benefit from breast tumour genomic data obtained during the last decade. The aim was to develop a user-friendly, web-based application, based on DNA microarrays results, called "breast cancer Gene-Expression Miner" (bc-GenExMiner) to improve gene prognostic analysis performance by using the same bioinformatics process. bc-GenExMiner was developed as a web-based tool including a MySQL relational database. Survival analyses are performed with R statistical software and packag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
268
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 333 publications
(271 citation statements)
references
References 22 publications
2
268
0
1
Order By: Relevance
“…The phosphorylation of cortactin releases cofilin and leads to the increase of polymerizing actin barbed ends (Oser et al, 2009). By performing prognostic analyses of gene expression in cohorts of breast cancer patients (bc-GenExMiner v3.0; http://bcgenex.centregauducheau.fr; Jézéquel et al, 2012) we found that the overexpression of both CTTN [P,0.0001; hazard ratio (a measure of survival in patients with the condition compared with that of those without), 1.49, 95% confidence interval, 1.26-1.70] and CFL1 (P,0.0001; hazard ratio 1.40, 95% confidence interval, 1.19-1.64) genes were associated with a reduced survival without metastatic relapse (supplementary material Fig. S3A,B) indicating the crucial role of these proteins in cancer cell invasion and the development of metastases.…”
Section: Resultsmentioning
confidence: 99%
“…The phosphorylation of cortactin releases cofilin and leads to the increase of polymerizing actin barbed ends (Oser et al, 2009). By performing prognostic analyses of gene expression in cohorts of breast cancer patients (bc-GenExMiner v3.0; http://bcgenex.centregauducheau.fr; Jézéquel et al, 2012) we found that the overexpression of both CTTN [P,0.0001; hazard ratio (a measure of survival in patients with the condition compared with that of those without), 1.49, 95% confidence interval, 1.26-1.70] and CFL1 (P,0.0001; hazard ratio 1.40, 95% confidence interval, 1.19-1.64) genes were associated with a reduced survival without metastatic relapse (supplementary material Fig. S3A,B) indicating the crucial role of these proteins in cancer cell invasion and the development of metastases.…”
Section: Resultsmentioning
confidence: 99%
“…Medians were compared using the Mann-Whitney U-test for non-normally distributed data, while means were compared using the two-sample t-test for normally distributed data. Kaplan Meier survival curves were produced from online expression databases KMplot (16) and Gene Expression Miner (17). Gene Expression Miner also used publically available expression data to produce a boxplot correlation of FST mRNA level with tumour grade.…”
Section: Methodsmentioning
confidence: 99%
“…Unfortunately, many gene expression arrays previously used in breast cancer outcome studies lacked RIP3 probe sets. However, using the bc-GenExMiner tool designed by Jézéquel et al [36], we analyzed combined data available from 6 studies (1 166 patients). Patients with greater than median RIP3 mRNA expression had a higher probability (P < 0.0085) of metastatic relapse-free survival over a 10-year period ( Figure 5E).…”
Section: Rip3 Expression Is Lost In Primary Breast Cancersmentioning
confidence: 99%